Alocação de Infraestruturas Virtuais em data centers implementados com Redes Definidas por Software - Souza, Felipe Rodrigo de; Miers, Charles C.; Fiorese, Adriano; Koslovski, Guilherme (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC); 2017: Anais do XXXV Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos, 2017)
The virtualization of data centers combined with the SDN paradigm lead to the provisioning of new cloud services. Among the management challenges faced by a SDN-based cloud provider, this work improves the virtual infrastructure allocation problem with QoS requirements. First, the problem is modeled as a mixed integer programing. Thus, integer constraints are relaxed and rounding heuristics are discussed. Besides guaranteeing the QoS requirements, the results indicate a reduction on virtual network communication latency.